Using copper slag and fly ash stabilised with lime or cement as a road base material. Issue 2 (3rd April 2019) - Patel, Deepti; Kumar, Rakesh; Chauhan, Krupesh; Patel, Satyajit
Abstract : The aim of the study reported in this paper was to investigate the engineering characteristics of different mixes of copper slag and fly ash stabilised with lime or cement for use in the base layer of flexible highway pavements. The effects of fly ash content, binder content, curing period and wetting−drying cycles on unconfined compressive strength, indirect tensile strength, resilient modulus and permanent strain were studied. The indirect tensile strength was found to be 17% and 18% of unconfined compressive strength for the lime and cement mixes respectively. Mixes with 6% lime or cement content, which were found to satisfy both the strength and durability criteria suggested by Indian Road Congress, are therefore recommended for use in the base layer of flexible road pavements. The fitting of different existing models for predicting resilient modulus and permanent strain was compared and constants of the best-fitting model are presented. Based on a finite-element analysis of a five-layer flexible pavement system, pavements with mixes of copper slag, fly ash and lime or cement in the base layer were found to have up to 78% and 55% respectively higher service life compared to pavements with wet-mix macadam as the base material.